ANALISIS KEBUTUHAN MATERIAL BESI TULANGAN PADA STRUKTUR BETON BERTULANG DENGAN METODE BAR BENDING SCHEDULE PADA PROYEK PEMBANGUNAN SEKOLAH CITA HATI SURABAYA - Lintang Sinipat; Michella Beatrix (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
A construction project always requires project resources as a component in the construction process. There are five project resources, namely workers, methods, tools, costs and materials. Of the five components, material is one of the main raw materials that has a considerable influence in determining the cost of the project. There are various kinds of materials, one of which is reinforcing steel. Reinforcing iron has a high enough value so that this material must be calculated very carefully in order to get the optimal iron value. Because it has a high enough value in the process, it is necessary to plan the calculation of the iron. Starting from the calculation of the need for reinforcing steel. There are several methods to calculate the need for reinforcing steel, namely the (manual) approach method and the Bar Bending Schedule (BBS) method. Bar bending schedule (BBS) is a planning method for steel work which contains detailed information in the form of the shape of the bar, the length of the bar, dimensions and the amount of bar to be used in structural work. BBS produces iron requirements in units of rods which then produce units of weight. Where in this project the process has not used the BBS iron calculation method. Where in manual calculations it does not pay attention to the pattern of iron pieces, so iron cutting in the field has not optimally utilized the remaining pieces or waste material. In this study, researchers will make iron calculations using the bar bending schedule method and make iron cutting patterns drawn per floor on a floor plan with detailed lengths and the amount of iron to be used, taking into account the remaining or waste material referring to the RKS and Shop Drawings. used in the Cita Hati School Building Development Project in order to accurately obtain the results of the material requirements for reinforcing steel and the remaining iron material. By applying the bar bending schedule method, it can make it easier to supply steel materials to suit the plan. So by using the bar bending schedule in the calculation of reinforcing steel it is included in an effort to optimize reinforcement in the Cita Hati School Building Development Project.